The proportion of HIV disclosure to sexual partners among people diagnosed with HIV in China: A systematic review and meta-analysis - Peng Wenwen; Song Xiaohan; Zhang Ci; Chen Yuqing; Zhou Qidi; Välimäki Maritta Anneli; Li Xianhong (FRONTIERS MEDIA SA, 2022)
Background: Sexual behavior is one of the main routes of HIV/AIDS spread. HIV disclosure to sexual partners has been confirmed to be an important strategy for HIV/AIDS prevention and control. We conducted a systematic review and meta-analysis to pool proportions and characteristics of HIV disclosure to sexual partners among people diagnosed with HIV in China.
Methods: We searched eight databases and extracted the data on HIV disclosure to partners. Heterogeneity of the data was tested with I2. Published bias subjectively and objectively analyzed through the funnel plot and Egger's regression test. Subgroup analyses were performed to explore the variation in the proportion by sexual partnership types (unclassified, regular, casual sexual partners), whether being men who have sex with men (MSM), and when to diagnose. The sources of heterogeneity were analyzed. Sensitivity analysis was carried out to evaluate the stability of the results.
Results: Out of 3,698 studies, 44 were included in the review; 11 targeted on MSM. The pooled proportion of HIV disclosure to sexual partners was 65% (95% CI: 56%−75%; 34 studies). Sub-group analyses indicated the proportions of HIV disclosure to regular, casual and unclassified sexual partners were 63% (95% CI: 45%−81%; 31 studies), 20% (95% CI: 8%−33%; nine studies), and 66% (95% CI: 59%−73%; 14 studies), respectively. Fifty-seven percent (95% CI: 45%−69%; three studies) disclosed on the day of diagnosis, 62% (95% CI: 42%−82%; four studies) disclosed within 1 month, and 39% (95% CI: 2%−77%; four studies) disclosed 1 month later. Among MSM, the disclosure to regular male partners, regular female sexual partners, spouses, and casual partner were 47% (95% CI: 29%−65%; six studies), 49% (95% CI: 33%−65%; three studies), 48% (95% CI: 18%−78%; seven studies), and 34% (95% CI: 19%−49%; four studies), respectively.
Conclusions: The disclosure prevalence of people diagnosed with HIV to sexual partners still need improving in China, and it varies among partner types, key populations, and time being diagnosed. HIV disclosure strategies and procedures need to be developed more detailed and tailored based on the pain points of disclosure status, so as to ultimately prevent HIV transmission through sexual contact.